Investigation and differential diagnosis of Stafne bone cavities with cone beam computed tomography and magnetic resonance imaging: Report of two cases - Elif Tarim Ertas; Meral Yircali Atici; Fahrettin Kalabalik; Ozlem Ince (Wolters Kluwer Medknow Publications, 2015)
Stafne bone cavity (SBC), commonly known as Stafne bone cyst or defect is mostly asymptomatic, appearing as a unilateral, round or ovoid, radiolucent defect with thick and corticated border. Defects that are referred as pseudocysts generally occur in mandibular molar region, below the mandibular canal at the lingual side of the mandible and may grow slowly in time. They have been also located lingually in the anterior mandible above the mylohyoid muscle, and on the ascending ramus just inferior to mandibular condyle or very rarely buccal region of the ascending ramus. The aim of this case report is to present two unusual cases of SBC detected incidentally during radiographic examination with cone beam computed tomography and magnetic resonance imaging findings. In the first case, significant enlargement caused vestibular resorption of the buccal cortex, which is a rare finding with SBCs and in the second case the large bone resorption reached up to the mental foramen.